Non-Severe Preeclampsia and Subclinical Inflammation: A Study of Cyclophilin A, NF-κB, PARP- 1, and Apoptosis in Human Placentas - Resistantie, Novi; Wibowo, Noroyono; Prasmusinto, Damar; Jusman, Sri Widia Azraki; Yamin, Muhammad; Siregar, Nurjati Chairani; Prihartono, Joedo; Mose, Johannes Cornelius; Suhendro, Suhendro; Yunita, Ferdiana; Rosmanah, Lis; Margyaningsih, Nur Ita; Qotrunnada, Labibah; Roviqoh, Cindy Fawwaz; Rauf, Saidah (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: To compare the expression of CyP-A, NF-κB, PARP-1, and apoptotic index in Non-Severe Preeclampsia (NS-PE) and Normal Pregnancy (NP) and explore their roles in inflammation during preeclampsia.Methods: Conducted in Depok, Indonesia, the cross-sectional study involved 28 participants divided into NS-PE and NP groups based on ISSHP criteria. NP was defined as uncomplicated pregnancies at 38–40 weeks gestation. Placental weight was measured, and ELISA was used to assess biomolecule levels. Data were analyzed using T-tests or Mann-Whitney tests.Result: Maternal gestational age, body mass index, and leukocyte levels were significantly higher in NS-PE. The apoptotic index, measured by TUNEL assay, was also significantly elevated in NS-PE (41.56 ±24.87) compared to NP (23.96 ±18.79; p = 0.044). While CyP-A, PARP-1, and NF-κB levels were higher in NS-PE eventhough they were not statistically significant. Immunohistochemistry confirmed an overall increase in these molecules, supporting their clinical relevance.Conclusion: Despite the lack of statistical significance, increased inflammation and apoptosis in NS-PE may contribute to placental dysfunction and adverse pregnancy outcomes.Non-Severe Preeclampsia dan Inflamasi Subklinis: Studi CyP-A, NF-κB, PARP-1, dan Apoptosis pada Plasenta ManusiaAbstrak Tujuan: Penelitian ini bertujuan untuk mengetahui perbedaan ekspresi CyP-A, NF-κB, PARP-1, dan indeks apoptosis antara preeklamsia non-severe (NS-PE) dan kehamilan normal (NP), serta perannya dalam proses inflamasi pada preeklamsia.Metode: Metode penelitian yang digunakan dalam penelitian ini adalah cross-sectional. Penelitian ini dilakukan di Depok, Indonesia, dengan 28 partisipan yang dikelompokkan menjadi NS-PE dan NP berdasarkan kriteria ISSHP. Berat plasenta diukur dan kadar biomolekul dianalisis menggunakan ELISA. Uji T dan alternatif Mann-Whitney digunakan untuk analisis statistik.Hasil: Hasil penelitian menunjukkan bahwa usia kehamilan, indeks massa tubuh (IMT), dan kadar leukosit secara signifikan lebih tinggi pada NS-PE. Indeks apoptosis (TUNEL) juga lebih tinggi secara signifikan pada NS-PE (41,56 ±24,87) dibandingkan NP (23,96 ±18,79; p = 0,044). Kadar CyP-A, PARP-1, dan NF-κB lebih tinggi pada NS-PE meskipun tidak signifikan secara statistik, pemeriksaan IHK mengonfirmasi relevansi klinis peningkatan pada keseluruhan biomolekul tersebut. Kesimpulan: Meskipun signifikansi statistik rendah, peningkatan peradangan dan apoptosis pada NS-PE dapat menyebabkan disfungsi plasenta dan dampak buruk pada kehamilan.Kata kunci: Apoptosis; inflamasi; preeklamsia.